Examining the impacts of climate change on the livelihoods of fisher communities in the Lake Victoria zone region through a gender lens - Adam, Rahma; Ouko, Kevin; Osano, Philip; Amwata, Dorothy; Ndiema, Nicholas (2024)
This discussion brief explores the impacts of climate change on fishers’ livelihoods in Kenya’s Homa Bay and Migori counties and identifies priority actions for enhancing the resilience of climate-change vulnerable fisher communities, including women and youth.